MENGANALISIS TUTUPAN LAHAN DAN URBAN HEAT INDEX (UHI) YANG ADA DI KOTA PANGKALAN BUN - Anshari, Rifqi; Jauhari, Ahmad; Mufidah, Mufidah (Jurnal Hutan Tropis, 2024)
Urban forest planning is not without obstacles, and one of them is the lack of research on the urban forest planning of the Mendawai Seberang Subdistrict, particularly in Pangkalan Bun City as a whole. Therefore, there is a need for spatial research aimed at determining whether the location of the urban forest plan aligns with the West Kotawaringin Regency Spatial Planning 2017-2037 and the criteria for urban forests based on Government Regulation No. 3 of 2002 on Urban Forests. Additionally, an analysis of land cover and the Urban Heat Index (UHI) in the urban forest plan location is also supported. The objective of this research is to evaluate the land cover and Urban Heat Index (UHI) in Pangkalan Bun City. The purposive sampling method was used, with a total of 50 survey points. The results of this research indicate that the land cover in the research location consists of Mixed Residential Buildings, Swamp/Peatland Forests, Scrubland, Rivers, and Seasonal Dryland Crops. Based on the survey results, the accuracy test calculation using the Kappa method shows that the kappa value in this research is 0.86, which is considered good as it approaches 1. Furthermore, the land cover has an impact on temperature increase in the study area.